Putting Environmental Infographics Center Stage: The Role of Visuals at the Elaboration Likelihood Model's Critical Point of Persuasion. (February 2015) - Lazard, Allison; Atkinson, Lucy
Infographics, which integrate visuals and text, can increase audience engagement with message content. Relying on two experiments, this study demonstrates the role of visuals for decisions to critically evaluate pro-environmental messages. Using the Elaboration Likelihood Model as a theoretical foundation, we demonstrate that individuals engage in greater levels of issue-relevant thinking when shown infographics compared to messages that rely just on text or just on illustration, with learning preferences and visual literacy as moderators. The findings demonstrate that visual content is an important factor for persuasive message processing, and infographic messages hold opportunities for the communication of environmental issues.